Grazing alters insect visitation networks and plant mating systems. (6th December 2013) - Vanbergen, Adam J.; Woodcock, Ben A.; Gray, Alan; Grant, Fiona; Telford, Annika; Lambdon, Phil; Chapman, Dan S.; Pywell, Richard F.; Heard, Matt S.; Cavers, Stephen; Brody, Alison
Summary Many flowering plant species have a facultative or obligate dependence on insect pollination for reproductive success. Anthropogenic disturbance may alter these species interactions, but the extent to which structural changes to plant‐pollinator networks affect plant species mating systems is not well understood. We used long‐term livestock grazing of a birch wood ecosystem to test whether disturbance of this semi‐natural habitat altered floral resources, the structure of plant–insect visitation networks and the mating system of a focal plant species, Cirsium palustre. Grazed habitat had a higher species richness of floral resources for pollinators. Visitation networks in grazed habitats were larger, more diverse, with an increase in the number of pollinators per plant species. Controlling for sampling effects, however, showed networks in grazed habitats were less nested and revealed a positive correlation between network connectance and floral species richness. Network connectance was negatively related to C. palustre outcrossing rate within grazed and ungrazed sites. However, on average, the effects of grazing, including greater mean connectance, produced higher overall outcrossing rates and more pollen donors compared with ungrazed habitat. The number of different pollen donors, spatial genetic structure and mating among close relatives were all correlated with greater extent of suitable C. palustre habitat in the landscape, consistent with the effects of increasing plant population size but limited seed dispersal. Pre‐adaptation of C. palustre to disturbance coupled with a preponderance of highly dispersive flies attracted to the greater food resources in grazed habitat is a likely mechanism underpinning this increased pollen transport. Habitat modification by long‐term mammalian grazing fundamentally shifted visitation network structure and the state of a plant mating system, indicating how ecosystem disturbance can cascade across levels of biological organization through altered interspecific interactions. Cirsium palustre retains flexibility to bias reproduction towards selfing where pollen donor diversity is limited; such reproductive flexibility may be an important mechanism structuring plant populations in human‐modified landscapes.